On the Duality between MIMO Systems with Distributed Antennas and MIMO Systems with Colocated Antennas. (9th December 2007) - Mietzner Mietzner, Jan Jan; Hoeher Hoeher, Peter A. Peter A.
Abstract : Multiple-input multiple-output (MIMO) systems are known to offer huge advantages over single-antenna systems, both with regard to capacity and error performance. Usually, quite restrictive assumptions are made in the literature on MIMO systems concerning the spacing of the individual antenna elements. On the one hand, it is typically assumed that the antenna elements at transmitter and receiver are colocated, that is, they belong to some sort of antenna array. On the other hand, it is often assumed that the antenna spacings are sufficiently large, so as to justify the assumption of uncorrelated fading on the individual transmission links. From numerous publications it is known that spatially correlated links caused by insufficient antenna spacings lead to a loss in capacity and error performance. We show that this is also the case when the individual transmit or receive antennas are spatially distributed on a large scale, which is caused by unequal average signal-to-noise ratios (SNRs) on the individual transmission links. Possible applications include simulcast networks as well as future mobile radio systems with joint transmission or reception strategies. Specifically, it is shown that there is a strong duality between MIMO systems with colocated antennas (and spatially correlated links) and MIMO system with distributed antennas (and unequal average link SNRs). As a result, MIMO systems with distributed and colocated antennas can be treated in a single, unifying framework. An important implication of this finding is that optimal transmit power allocation strategies developed for MIMO systems with colocated antennas may be reused for MIMO systems with distributed antennas, and vice versa.